Gas‐water energy conversion efficiency in two‐phase vertical downflow. Issue 4 (13th June 2018) - Sun, Yang; Yao, Yuting; Fan, Yawen; Su, Junwei; Luo, Zhaoyang; Lan, Peng; Bao, Yan
Abstract: An automatic pump is developed using low water‐head hydropower. The energy conversion efficiency η of the gas‐water energy conversion equipment is the focus. In this equipment, low‐head water normally drains to the vertical downcomer. When water particles separate via gravity, a vacuum is generated, and air is mixed into the water spontaneously. High‐pressure gas is ultimately produced at the end of the pipe. To discuss the effects of the air intake pipe diameter, river drop and water flow rate on η, a full‐scale experiment is conducted, and an analytical solution based on the separation of water particles is derived. The air intake pipe diameter has almost no effect on η, but η changes dramatically as the water flow rate varies. Meanwhile, η initially increases and then decreases as the river drop increases. These findings enable the development of a method for low water‐head hydropower utilization. Abstract : Mechanisms of the interaction between air and water in two‐phase vertical downflow. Effects of several factors on the energy conversion efficiency of the new equipment. An analytical solution based on the water particles separation is derived.